2005
DOI: 10.2135/cropsci2004.0104
|View full text |Cite
|
Sign up to set email alerts
|

Inheritance of Seed Zinc Accumulation in Navy Bean

Abstract: a correlation between high phytate diets and limited Zn absorbance in the gastrointestinal tract of humans and Human zinc (Zn) deficiency is a widespread condition prevalent in animals (Saha et al., 1994; House et al., 1982; Turnlund people consuming grain and legume based diets. Dry beans (Phaseolus vulgaris L.) are frequently the major protein source in such diets. et al., 1984;Lonnerdal et al., 1989; Hunt et al., 1998; One way to reduce the incidence of Zn deficiency may be through Zhou et al., 1992). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
60
4
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(74 citation statements)
references
References 29 publications
7
60
4
2
Order By: Relevance
“…The broad-sense heritability of the zinc concentrations of Andean common bean seeds had a high magnitude (h 2 b= 63.36 to 72.22%), and the narrow-sense heritability had an intermediate (h 2 n= 31.04%; IAC Boreal × Light Red Kidney) to high (h 2 n= 63.60%; Ouro Branco × Light Red Kidney) magnitude. The variation range that was obtained for the broad-sense and narrow-sense heritability estimates of zinc concentrations was similar to that found for Middle American common bean seeds by Rosa et al (2010) and was inferior to the estimates reported by Cichy et al (2005). In this study, a high narrow-sense heritability was observed for the zinc concentration in the cross Ouro Branco × Light Red Kidney, indicating the predominance of additive variance.…”
Section: Inheritance Pattern Heritability and Heterosissupporting
confidence: 75%
See 3 more Smart Citations
“…The broad-sense heritability of the zinc concentrations of Andean common bean seeds had a high magnitude (h 2 b= 63.36 to 72.22%), and the narrow-sense heritability had an intermediate (h 2 n= 31.04%; IAC Boreal × Light Red Kidney) to high (h 2 n= 63.60%; Ouro Branco × Light Red Kidney) magnitude. The variation range that was obtained for the broad-sense and narrow-sense heritability estimates of zinc concentrations was similar to that found for Middle American common bean seeds by Rosa et al (2010) and was inferior to the estimates reported by Cichy et al (2005). In this study, a high narrow-sense heritability was observed for the zinc concentration in the cross Ouro Branco × Light Red Kidney, indicating the predominance of additive variance.…”
Section: Inheritance Pattern Heritability and Heterosissupporting
confidence: 75%
“…A continuous distribution of the iron and zinc concentrations in common bean seeds was previously described in early (Possobom et al, 2015) and advanced (Blair, Astudilo, Grusak, Graham, & Beebe, 2009;Cichy, Caldas, Snapp, & Blair, 2009;Blair et al, 2010b;Ribeiro et al, 2014b;Teixeira, Lima, Abreu, & Ramalho, 2015) generations in recombinants that were obtained from the crosses Andean × Andean, Andean × Middle American and Middle American × Middle American. These results affirm that the iron and zinc concentrations in common bean present quantitative inheritance in populations of low and high homozygosity, regardless of the gene pool, and that they oppose the initial hypothesis of Cichy et al (2005) regarding the monogenic control of the zinc concentration in common bean seeds.…”
Section: Inheritance Pattern Heritability and Heterosissupporting
confidence: 69%
See 2 more Smart Citations
“…It was postulated that the zinc content in the navy bean seeds was controlled by a single dominant allele and additive gene action was responsible for most of the observed (Cichy et al 2005). In this case, a dominant monogenic inheritance and high heritability for zinc content was verified.…”
Section: Introductionmentioning
confidence: 86%